2011
DOI: 10.1371/journal.pone.0027472
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between ROS Homeostasis and Secondary Metabolism in S. natalensis ATCC 27448: Modulation of Pimaricin Production by Intracellular ROS

Abstract: Streptomyces secondary metabolism is strongly affected by oxygen availability. The increased culture aeration enhances pimaricin production in S. natalensis, however the excess of O2 consumption can lead to an intracellular ROS imbalance that is harmful to the cell. The adaptive physiological response of S. natalensis upon the addition of exogenous H2O2 suggested that the modulation of the intracellular ROS levels, through the activation of the H2O2 inducible catalase during the late exponential growth phase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 63 publications
0
43
0
1
Order By: Relevance
“…In addition, hydroxypyruvate has been proposed to increase the levels of intracellular glycolaldehyde, which is further oxidized to glyoxal; this process is accompanied by a large amount of ROS formation (35). The presence of ROS in the cell not only triggers an adaptive response to scavenge these toxic molecules and repair molecular damage but also plays a role as secondary messenger in cell signaling (36,37). The restoration of antibiotic production to the wild-type levels in the double mutant strain LN-RH supports this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, hydroxypyruvate has been proposed to increase the levels of intracellular glycolaldehyde, which is further oxidized to glyoxal; this process is accompanied by a large amount of ROS formation (35). The presence of ROS in the cell not only triggers an adaptive response to scavenge these toxic molecules and repair molecular damage but also plays a role as secondary messenger in cell signaling (36,37). The restoration of antibiotic production to the wild-type levels in the double mutant strain LN-RH supports this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…AllB, Alc, Ugl, AceB1, Gcl, GlxR, and Hyi correspond to allantoinase, allantoicase, ureidoglycolate lyase, malate synthase, glyoxylate carboligase, tartronate semialdehyde reductase, and hydroxypyruvate isomerase activities, respectively. (37). Cross talk between ROS homeostasis and secondary metabolic programs has been demonstrated in S. natalensis ATCC 27448 (37) and S. clavuligerus (39).…”
Section: Figmentioning
confidence: 99%
“…Besides, the rimA1-disrupted mutant was also tested for its ability to produce OTC under oxidative stress, which is induced by H 2 O 2 (Beites et al 2011;Ahn et al 2012). H 2 O 2 was added to the liquid MM + gly before inoculation at the final concentration of 2 mM.…”
Section: Biosynthesis Of Otc By the Rima1-disrupted Mutant Under Diffmentioning
confidence: 99%
“…Oxidative stress is common response to all aerobic organisms, but it is particularly pronounced in industrial biosynthetic processes for secondary metabolite production, where high intensity of oxygenation (aeration) is applied (Beites et al 2011). A number of studies demonstrated that adaptive response of oxidative stress does not only have "defense role", but also has impact on the regulation of secondary metabolism.…”
Section: Impact Of Rima1 Disruption On Otc Production When S Rimosusmentioning
confidence: 99%
“…Though the mechanism remains unclear, H 2 O 2 indeed induces the biosynthesis of secondary metabolites, such as pimaricin, validamycin, and spinosad, etc. [Beites et al, 2011;Wei et al, 2011;Zhang et al, 2014]. Knowledge of whether the addition of various vegetable oils generates oxidative stress and how the oxidative stress influences spinosad biosynthesis in S. spinosa would be meaningful to the optimization of the fermentation process.…”
Section: Introductionmentioning
confidence: 99%